Determinants of Internal Control Systems on the Financial Performance of Billboard Tax (Badan Pengelola Pajak dan Retribusi Daerah Kota Jambi) - Febro, Zahra Rasyanda; Sam, Iskandar; Tiswiyanti, Wiwik (Indonesian Journal of Economic & Management Sciences, 2024)
This study aims to identify the extent of the impact of control environment, risk assessment, control activities, information and communication, and monitoring processes on financial performance. A descriptive quantitative approach is applied in this research. The sample is purposively selected based on specific criteria, with primary data collected through distributed questionnaires. For data analysis, the study utilizes descriptive statistics and multiple linear regression with SPSS 29 software. The findings reveal that, partially, the control environment has a positive and significant effect on financial performance, while risk assessment shows no significant impact on financial performance. Additionally, control activities have a positive and significant effect on financial performance, whereas information and communication, as well as monitoring, do not show a significant impact on financial performance.